Effect Of Temperature Towards Membrane Fouling By Microalgae Algal Organic Matter - Ragupathy, Sukdarsanan (Universiti Sains Malaysia, 2021)
Marine algae produce algal organic matter (AOM) which were found to be the cause in membrane fouling. Many studies shown that algae, cause significant releases of AOM into water extracellularly and intracellularly through cell lysis. Membrane distillation (MD) is a new thermally-driven technology that has a lot of potential in desalination, water and wastewater treatment, and other applications. The viability of MD for various applications has been improved thanks to advancements in membrane design and the utilisation of alternate energy sources. Fouling of membranes, on the other hand, is still a key issue that plagues MD's long-term stability. In this study, AOMs, which are soluble extracellular polymeric substance (sEPS) and bounded EPS (bEPS) two benthic species (Amphora coffeaeformis and Navicula incerta) were exposed to a temperature range to stimulate membrane processes and hollow fire PP membranes were soaked during the heating process to study the effect on the membrane fouling at high temperatures. The EPS of benthic diatom species were extracted andwere characterized by using colourimetric analysis where for carbohydrate analysis, the phenol-sulphuric acid method was used to measure the carbohydrate concentration andfor protein analysis, the bicinchoninic acid (BCA) method was used to determine the protein concentration. The characterization of the EPS was done after the algal were harvested at room temperature and exposed to temperatures 60℃, 70℃ and 80℃ for 8 hours. Similarly, the membranes were soaked during the heating process and collected after the heating for characterization. This study will help in determining the characteristic of EPS released by algal cells at a higher temperature during the MD processes. When the temperature exposed to the EPS increased from room temperature to 60℃, the protein concentration in bEPS increased from 340.74 ± 33.10μg/g to 343.27± 32.03μg/g for N. incerta and 279.75 ± 88.78μg/g to 338.89 ± 119.51μg/g for A. coffeaeformis. The highest bEPS protein concentration of 375.58 ± 51.58μg/g for N. incerta was obtained at 80℃ and for A. coffeaeformis highest of 338.89 ± 119.51μg/g was obtained at 60℃. For sEPS the trends were different between the species with the increasing temperature where the highest protein concentration of 356.41 ± 185.16μg/g for A. coffeaeformis was obtained at room temperature and for N. incerta highest of 321.59 ± 68.89μg/g was obtained at 60℃. The carbohydrate concentration in sEPS and bEPS varies at different temperatures in different species and cannot be generalized for every algal species. However, the highest carbohydrate concentration in N. incerta for both sEPS and bEPS were obtained at 70℃ with values 679.30 ± 230.46μg/g and 883.69± 51.70μg/g respectively. For A. coffeaeformis, the highest carbohydrate concentration in sEPS and bEPS were 310.194 ± 38.31μg/g at 70℃ and 540.56 ± 232.79μg/g at 28℃ respectively. Moreover, from the membrane analysis, the contact angle reduces as the temperature increases for EPS of both species. The contact angle for membrane soaked in sEPS and bEPS of A. coffeaeformis reduced by 17% and 59% respectively when temperature increased from room temperature to 80℃. For membrane soaked in sEPS and bEPS of N. incerta, the contact angle reduced by 29% and 72% respectively when temperature increased from room temperature to 80℃. The comparison between SEM images showed that bEPS contributes more severe fouling compared to sEPS. Furthermore, increasing the temperature increases the fouling of the membrane for both sEPS and bEPS. Overall, the compositions of protein in the soluble EPS and bound EPS at different temperatures will likely dictate the severity of fouling in MD operations.